ANALISIS PENGARUH PENERIMAAN PAJAK PENGHASILAN, PAJAK BUMI DAN BANGUNAN, DAN PERTUMBUHAN EKONOMI TERHADAP KESENJANGAN PENDAPATAN PADA PEMERINTAH PROVINSI DI INDONESIA - Fitri, Ellena Novia; Yulsiati, Henny; Aryani, Yuli Antina (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of this study is to determine how the income tax variable, the land and building tax variable, and the economic growth variable affect the income gap variable. Income inequality is also significantly affected by land and building tax variables, income tax variables, and economic growth. It is hoped that the findings from this study will assist in the development of more progressive tax laws and improve the effectiveness and efficiency of tax administration. In addition, it is hoped that the government can expand income distribution across national and regional boundaries, lower poverty rates, and accelerate economic growth.